On best acoustical parameters' values for 'Liederistic' music performance: A preliminary study. Issue 4 (December 2021) - Domenighini, P.
'Liederistic' music is a musical genre on which architectural acoustical research is rarely focused. Despite this lack of scholarship, however, this genre represents one of the most interesting challenges for acoustical problem solving. In fact, it combines speech and music comprehension requirements in a fascinating manner to illuminate elements of both the magnification of the musical score and the hidden tension of a sung poetry text. To individualise the main characteristics of this genre, a multidisciplinary approach is taken, starting from a musical point of view. A knowledge and comprehension of music is a fundamental step to determine the parameters that allow for the best performance and listening experience of this particular music. Consequently, an introduction to the physics and acoustical characteristics of the singing voice and the piano is given, specifically highlighting the technological development of the piano since the 18th century. Through a combination of historical, architectural, and interior design research, a possible location of the original performance is recreated to investigate the probable primal acoustic conditions using computational analysis. Various contemporary chamber music halls were then considered and compared to the reconstructed location to investigate whether actual places exist with similar acoustic conditions.